A realidade (social) está estruturada como ideologia: investigações sobre o conceito de ideologia entre Marx e a Psicanálise - Carvalho, Mayra Carneiro de (2019)
Starting from the claim made by Jacques Lacan in the 1970s that it was Karl Marx who invented the symptom with his conception of the transition from feudalism to the capitalist mode of production, we first propose to investigate the constitution of Marx's critical method. This culminates in the analysis of the commodity form and its fetishist character, as a symptom of capitalism, taken from Marx’s theory of surplus-value. This theory provides an explanation of how accumulation takes place within bourgeois society, thus presupposing an original accumulation that would have given rise to the characteristic industrial production of capitalism. In describing how this “primitive accumulation” took place, Marx invents the notion of symptom associated with commodity fetishism, as Slavoj Žižek demonstrates. Commodity fetishism, on the other hand, embodies the characteristic inversion of material production in the capitalist regime, which is the core of his concept of ideology. Freud, in his dream analysis, uses an interpretive method homologous to what Marx uses to address commodity fetishism. The inversion own to it has the form of an illusion constituting the economic relations governed by the logic of the commodity, but present in other areas of social life, such as the relationship of individuals to the state. Here we approach Freud's notion of illusion in dealing with religious ideas and follow his suggested direction about the possible illusory nature of the relationship of individuals to the state. Thus, an exposition about the historical origin as well as the very own nature of the state and its legal apparatus is important within the critique of ideology. We come, then, to the actuality of the task of the critique of ideology, even within the psychoanalytic field. Finally, we succinctly explore the status of ideology in the so-called postmodernity, or more precisely in late capitalism.